THE EFFECT OF FUN ATHLETICS EXERCISES ON PSYCHOMOTOR DEVELOPMENT - GÜLER, Mustafa; BAYAZIT, Betül; YILMAZ, Ozan; ONGÜL, Ece (Sportif Bakış: Spor ve Eğitim Bilimleri Dergisi, 2017)
The purpose of this research was to investigate the effect of fun athletics exercises on the psychomotor development. The research group consisted of 9 boys and 27 girls with a total of 36 students between 11-14 ages in Kocaeli. In the study, the fun athletics exercises (featured somersault, obstacles to jump, slip under the barrier, slalom, training ladder, double jump, medicine ball handling) applied for 90 minutes a day and 3 days a week over 8 weeks. The data was analyzed with Wilcoxon Matched Pairs Test and significance level was determined as α=0.05. According to findings of this study significant differences were found between pre and post tests results. As a result this study showed that fun athletic exercises have a positive effect on 11-14 aged children’s psychomotor development.